Synthesis and anti-mitotic activity of 2,4- or 2,6-disubstituted- and 2,4,6-trisubstituted-2H-pyrazolo[4,3-c]pyridines - Milišiūnaitė, Vaida; Arbačiauskienė, Eglė; Řezníčková, Eva; Jorda, Radek; Malínková, Veronika; Žukauskaitė, Asta; Holzer, Wolfgang; Šačkus, Algirdas; Kryštof, Vladimír (European journal of medicinal chemistry, 2018)
An efficient synthetic route for the synthesis of 2H-pyrazolo[4,3-c]pyridines, primarily varying by the substituents at the 2-, 4- and 6-positions, is described here. A Sonogashira-type cross-coupling reaction was employed to yield 3-alkynyl-1H-pyrazole-4-carbaldehydes, ethanones and propanones from the corresponding 1H-pyrazol-3-yl trifluoromethanesulfonates. Subsequent treatment of the coupling products with dry ammonia afforded a versatile library of 2H-pyrazolo[4,3-c]pyridines, which were then evaluated for their cytotoxicity against K562 and MCF-7 cancer cell lines. The most potent of these compounds displayed low micromolar GI50 values in both cell lines. Active compounds induced dose-dependent cell-cycle arrest in mitosis, as shown by flow cytometric analysis of DNA content and phosphorylation of histone H3 at serine-10. Moreover, biochemical assays revealed increased activities of caspases-3/7 in treated cells, specific fragmentation of PARP-1, and phosphorylation of Bcl-2, collectively confirming apoptosis as the mechanism of cell death.
Keywords: Mitosis; Cell Death; Antimitotic Agents; pyridiny; Molecular Structure; Antineoplastic Agents; Drug Screening Assays, Antitumor; lidé; Cell Cycle Checkpoints; screeningové testy protinádorových léčiv; buněčná smrt; mitóza; MCF-7 Cells; MFC-7 buňky; Cell Proliferation; Dose-Response Relationship, Drug; proliferace buněk; Humans; Pyridines; antimitotika; molekulární struktura; Structure-Activity Relationship; K562 Cells; protinádorové látky; kontrolní body buněčného cyklu; vztah mezi dávkou a účinkem léčiva; buňky K562; vztahy mezi strukturou a aktivitou